Direct Organogenesis of Passiflora foetida L. through Nodal Explants - Anand, S.P.; Jayakumar, E.; Jeyachandran, R.; Nandagobalan, V.; Doss, A. (Plant Tissue Culture and Biotechnology, 2012)
DOI: http://dx.doi.org/10.3329/ptcb.v22i1.11266 Plant Tissue Cult. & Biotech. 22(1): 87-91, 2012 (June)